2018
DOI: 10.1002/ps.4845
|View full text |Cite
|
Sign up to set email alerts
|

Reduced translocation in 2,4‐D‐resistant oriental mustard populations (Sisymbrium orientale L.) from Australia

Abstract: Resistance to 2,4-D in oriental mustard is likely due to reduced translocation of 2,4-D out of the treated leaf. Inheritance of 2,4-D resistance is conferred by a single gene with a high level of dominance. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Non‐target site resistance mechanism(s) such as reduced absorption and/or translocation have been previously reported to confer 2,4‐ D resistance in multiple species . Therefore, we conducted experiments to determine differences in absorption and translocation of 2,4‐ D in plants of MO‐Ren and MO‐S biotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐target site resistance mechanism(s) such as reduced absorption and/or translocation have been previously reported to confer 2,4‐ D resistance in multiple species . Therefore, we conducted experiments to determine differences in absorption and translocation of 2,4‐ D in plants of MO‐Ren and MO‐S biotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The plants of both MO‐Ren and MO‐S biotypes exhibited rapid absorption of [ 14 C] 2,4‐ D and about 70% of the applied herbicide was absorbed within 24 h of treatment. Various environmental, species and application factors can affect 2,4‐ D absorption and previous research has shown that 2,4‐ D absorption can range from 10% to 99% in different species …”
Section: Resultsmentioning
confidence: 99%
“…Two populations P40 and S1 were selected for the inheritance study. Generation of F 1 and F 2 seeds were conducted using the method described by Dang et al 8 Briefly, five survivors of P40 at 800 g ha −1 diflufenican and five untreated plants of the S1 were grown in individual 8.5 L pots in a glasshouse (15 to 22 ∘ C), watered and fertilized as required. Three days after the first flower opened, all mature siliques, opened flowers and small buds were removed from each inflorescence and only two to three young buds retained.…”
Section: Inheritance Of Resistance To Diflufenican 251 Generation Omentioning
confidence: 99%
“…1,4 Oriental mustard is usually easy to control with herbicides, but has recently evolved resistance in Australia to several herbicide groups that include acetolactate synthase (ALS) inhibitors, synthetic auxins, phytoene desaturase (PDS) inhibitors and photosystem II inhibitors. [5][6][7][8][9] Diflufenican and picolinafen are pyridinecarboxamide herbicides belonging to Group 15 (WSSA designation), which inhibit carotenoid biosynthesis. Diflufenican was developed in 1979 and has been used as a pre-emergent and early post-emergent herbicide for the selective control of certain broadleaf weeds, especially brassicaceae family, in winter cereals since the mid-1980s.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, reduced SAH absorption and/or translocation has been related to the resistance response in several dicotyledonous weeds species [12]. More recently, the lack of 2,4-D translocation has also been reported in R biotypes of Papaver rhoeas [13], Sisymbrium orientale [14] and Raphanus raphanistrum [15].…”
Section: Introductionmentioning
confidence: 96%